An empirical investigation of macroeconomic determinants of public debt in Ghana - Ibrahim Musah (Cogent Economics & Finance, 2023)
Ghana has a lengthy history of accumulating public debt, primarily driven by the expansion of fiscal deficits. This has resulted in a persistent increase in the public debt ratio, as the country borrowed both externally and internally to stimulate economic growth and augment its capital stock. However, this trajectory has led to concerns about debt sustainability. The study examines the macroeconomic determinants of public debt accumulation in Ghana. It aims to analyse these determinants' short- and long-term effects using the autoregressive distributed lag (ARDL) model. The study finds a positive association between merchandise trade and public debt, indicating that an increase in trade due to heavy reliance on external trade to meet domestic consumption needs leads to a rise in public debt. Furthermore, it identifies a positive relationship between gross fixed capital formation (growth) and public debt, indicating that as the economy grows and more capital is invested in fixed assets, public debt also increases. The study also reveals that higher interest payments contribute to a greater accumulation of public debt. It further demonstrates that government spending plays a crucial role in shaping the trajectory of public debt, as an increase in spending leads to an increase in public debt. The findings suggest that fiscal policies, external borrowing, trade, interest payments, and budget deficits substantially influence public debt levels in Ghana. As a result, the study highlights the need for policies that promote fiscal discipline, debt sustainability, and transparency to manage public debt effectively.
Keywords: 330; budget deficit; debt sustainability; economic growth; public debt